Determinants of commercialization of innovative technologies - Kobielieva, A. V. (Луцький національний технічний університет, 2022)
It is proposed to develop two separate plans for the commercialization of both technologies and innovations. This will allow more efforts to be directed to the creation of new knowledge directly, and not to the improvement of old ones, since innovation is an activity aimed at creating fundamentally new products and services that did not exist before. Of course, the process of commercialization of technologies should also develop at an active pace, as this will increase the competitiveness of existing products on the market.
Keywords: innovative technologies; intellectual property; commercialization; influencing factors; industrial enterprises